2018
DOI: 10.1093/ecco-jcc/jjy117
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA Methylation in Treatment-naïve Ulcerative Colitis

Abstract: Background and AimsThe aim of this study was to investigate the genome-wide DNA methylation status in treatment-naïve ulcerative colitis [UC], and to explore the relationship between DNA methylation patterns and gene expression levels in tissue biopsies from a well-stratified treatment-naïve UC patient group.MethodsMucosal biopsies from treatment-naïve patients [n = 10], and a healthy control group [n = 11] underwent genome-wide DNA bisulfite sequencing. Principal component analysis [PCA] and diverse statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 82 publications
3
39
0
Order By: Relevance
“…SLC26A4 encodes pendrin, an anion exchange protein whose clinical relevance is mostly described within the context of hearing impairment [74]. Nonetheless, whole genome bisulfite sequencing and RNA-sequencing analysis of mucosal biopsies of UC patients with non-UC patients indicated promoter hypomethylation and upregulated expression [63], which is in agreement with the observations made in this study. MPEG1 encodes Perforin-2, which is a protein expressed in phagocytes involved in the innate immune response by forming pores in bacteria [75,76].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SLC26A4 encodes pendrin, an anion exchange protein whose clinical relevance is mostly described within the context of hearing impairment [74]. Nonetheless, whole genome bisulfite sequencing and RNA-sequencing analysis of mucosal biopsies of UC patients with non-UC patients indicated promoter hypomethylation and upregulated expression [63], which is in agreement with the observations made in this study. MPEG1 encodes Perforin-2, which is a protein expressed in phagocytes involved in the innate immune response by forming pores in bacteria [75,76].…”
Section: Discussionsupporting
confidence: 91%
“…We reported previously that SERPINF1 was differentially methylated and expressed when comparing ileal fibroblasts obtained from stenotic tissue with non-inflamed tissue from CD patients [62]. Similarly, PRAP1 was found to be hypermethylated and downregulated in mucosal biopsies obtained from treatment naïve UC patients relative to control patients [63]. At the level of genomics, a meta-analysis suggested that the GSTT1 null mutation was significantly associated with susceptibility to IBD [64].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, this is part of the transomic Advanced Study of In ammatory Bowel disease (ASIB) study where parallel studies of the epigenome, transcriptome, proteome and metabolome are ongoing. 33,[41][42][43][44][45] . This transomic approach at debut of UC will be performed and correlated to long-term clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding UC patients, Kang et al also found differentially methylated patterns in UC patients with 3 genes, FAM217B, KIAA1614 and RIBC2, being hypermethylated; thus, this might be a tool for distinguishing UC patients from healthy individuals [72]. In a recent study, mucosal biopsies taken from UC patients showed different methylation patterns from those of healthy individuals; UC patients showed hyper-methylation or hypo-methylation in genes involved in homeostasis and defense, or in immune response pathways, respectively [73]. An epigenome-wide association study revealed that IBD patients bear differentially methylated positions (DMPs) compared with healthy individuals and most of these DMPs found in IBD cases were shared between CD and UC patients.…”
Section: Epigenomics In Ibdmentioning
confidence: 95%